Factors affecting bowel gangrene development in patients with sigmoid volvulus - Sabri Selcuk Atamanalp (Annals of Saudi Medicine, 2013)
BACKGROUND AND OBJECTIVES: Sigmoid gangrene develops in 6.1% to 93.4% of sigmoid volvulus (SV) cases, and increases the mortality rate from 0% to 40% without bowel gangrene to 3.7% to 80%. This study aimed to investigate factors that induce bowel gangrene development in SV patients. DESIGN AND SETTINGS: Retrospective study from a single center. PATIENTS AND METHODS: We determined whether there was any correlation between sigmoid gangrene and the following factors: age, gender, a previous history of a volvulus, previous history of abdominal surgery, pregnancy, major comorbidities, shock, duration of symptoms, direction and degree of rotation of volvulus, and ileosigmoid knotting. RESULTS: Of 442 patients, 271 (61.3%) had sigmoid gangrene. The presence of pregnancy was negatively correlated with sigmoid gangrene development (P<.05), while comorbid diseases (P<.01), associated shock (P<.01), prolonged symptom duration (P<.05), overrotation (P<.05), and associated ileosigmoid knotting (P<.01) were positively correlated with bowel gangrene. However, no correlation was observed between sigmoid gangrene and the other studied factors. CONCLUSION: An inverse correlation between pregnancy and sigmoid gangrene was observed. On the other hand, a positive correlation was noted between bowel gangrene and comorbid diseases, shock, prolonged duration of symptoms, overrotation, and associated ileosigmoid knotting.